A note on the computation of the hamming bound. - Abaya, Efren F.
This paper derives a simple approximation to a binomial sum occuring in the Hamming Bound. The approximation is easy to compute and quite accurate, even for modest values of the parameteres involved. The approximation permits easy calculation of the minimum number of parity bits required for t error correction.